Colonic Endometriosis: A Case Report and Literature Review - Myo Thet Tin; Khin San Aye; Tint Lwin; Lin Lin Htun; Than Than Htwe (Asian Journal of Medicine & Health Sciences, 2022)
Endometriosis is characterized by the presence of normal endometrial mucosa that is implanted in sites other than the uterine cavity. It is commonly presented in women in reproductive age, seldom involving intestinal tract. We reported a case of colonic endometriosis presented with bleeding per rectum, coinciding with her cyclical bleeding. Colonoscopy showed surface mucosal inflammation at the rectosigmoid junction mimicking inflammatory bowel disease. Biopsy from the colonoscopy revealed the presence of endometrial tissue within colonic mucosa and submucosa. Colonic endometriosis should always be kept in mind as a differential diagnosis in women in reproductive-age, presenting with symptoms of gastrointestinal bleeding and abdominal pain during the menstrual period. A thorough literature review was conducted with emphasis on further diagnostic applications, complications and management.